Akupresur Sebagai Terapi Komplementer dalam Mengurangi Kecemasan pada Penderita Penyakit Tidak Menular: Narrative Review - Ni Made Laksmi Devi Jayanti. P; Made Suadnyani Pasek (Pusat riset dan Inovasi Nasional, 2026)
Non-communicable diseases (NCDs) are chronic health conditions that affect not only physical but also psychological well-being, including increased anxiety. Untreated anxiety can reduce quality of life and treatment adherence. Acupressure, as a form of complementary therapy, offers a safe and non-invasive approach to managing anxiety. This narrative review aims to evaluate the effectiveness of acupressure in reducing anxiety among patients with NCDs. Articles were searched using Google Scholar with keywords such as